Cournot's Dynamic Market Solution and Hosomatsu's Lemma: An Alternative Proof - Neudecker, H. (Review of Economic Studies, 1970)
Journal Article Cournot's Dynamic Market Solution and Hosomatsu's Lemma: An Alternative Proof Get access H. Neudecker H. Neudecker University of Birmingham, and Middle East Technical University, Ankara Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 37, Issue 3, July 1970, Pages 447–448, https://doi.org/10.2307/2296733 Published: 01 July 1970 Article history Received: 01 October 1969 Revision received: 01 January 1970 Published: 01 July 1970